Understanding Assertive Behavior in Junior High School Students: A Descriptive Perspective - Dias Fahmi Ilham; Agung Nugraha (Journal of Mental Health and Well-Being in Counseling, 2026)
Assertive behavior is an important social skill that adolescents need to possess in facing the demands of their social environment, particularly at school. This study aims to determine the general description of assertive behavior among students at SMP Negeri 21 Tasikmalaya and its implications for guidance and counseling services at the school. This study used a quantitative approach with descriptive methods. The research subjects were 279 students in grades VIII and IX selected using a total sampling technique. Data were collected through an assertive behavior scale that covers cognitive, affective, and psychomotor aspects and has met validity and reliability tests. Data analysis was conducted using descriptive statistics and independent difference tests. sample t- test with the help of the SPSS program. The results of the study indicate that students' assertive behavior is generally in the moderate category with an average score of 122 and a standard deviation of 12. This finding indicates that students have basic abilities in expressing opinions, feelings, and defending their rights appropriately, but have not been displayed consistently in various social situations. This condition reflects that students' assertive behavior is still in the development and strengthening stage. Overall, the results of the study indicate that students have quite good assertive potential and can be developed more optimally through a conducive educational environment.